Public Diplomacy and country-brand in the Americas: Approach to Brasil, Chile, México and Perú experiences. - Méndez-Coto, Marco Vinicio (2016)
This article characterizes the contemporary dissemination of public diplomacy strategies and country brand as tools of foreign policy in the Americas, claiming the existence of a positive correlation between higher relative power capabilities and a higher probability of developing a public diplomacy strategy. In contrast, country brand is a more common tool given the need of most American states to strengthen their integration into the world economy. Brazil, Chile, Mexico, and Peru are used as examples. This article is the result of the research project entitled “Diplomacia pública en Estados pequeños: perspectivas para Costa Rica,” code 0107-13, Universidad Nacional de Costa Rica.